Final Diagnosis in Patients Referred with a Diagnosis of Neuroretinitis. (2nd November 2015) - Kahloun, Rim; Khairallah-Ksiaa, Imen; Abroug, Nesrine; Mahmoud, Anis; Ben Yahia, Salim; Zaouali, Sonia; Jelliti, Bechir; Khairallah, Moncef
Abstract: The purpose of this study was to determine final diagnosis of patients referred with a diagnosis of neuroretinitis. A retrospective study of 40 patients with optic disc oedema with macular star (ODOMS) referred with a diagnosis of neuroretinitis was conducted. The final diagnosis was neuroretinitis in 26 patients (65%), with most of these patients (96.1%) having unilateral involvement. Main underlying aetiologies included cat scratch disease (30.8%), rickettsiosis (19.2%), and idiopathic neuroretinitis (23.1%). The remaining 14 patients (35%) had ODOMS that had been mistaken for neuroretinitis. Of these patients, 42.8% were found to have a previously unknown malignant systemic hypertension in association with bilateral ODOMS. Neuroretinitis, usually unilateral, should be differentiated from other causes of unilateral or most often bilateral ODOMS that may masquerade as neuroretinitis, mainly malignant systemic hypertension. This is essential to avoid inappropriate work-up and management and subsequent potential visual or systemic morbidity.